Low-cost time-lapse seismic imaging of CCS with the joint recovery model - Herrmann, Felix J.; Louboutin, Mathias; Yin, Ziyi; Witte, Philipp (IMAGE 2021, 2021)
Seismic monitoring of Carbon Capture & Storage (CCS) is often challenging because the time-lapse signal of the growth of CO2 plume is weak. This situation is compounded by the fact that surveys are often coarsely sampled and not replicated. Despite these challenges, we demonstrate, by means of a realistic synthetic experiment on the Compass model, that the CO2 plume is detectable when the baseline and monitor surveys are inverted jointly.
Workshop: Geophysical Challenges in Presalt Carbonates